Potential Role of Titanium Dioxide (TiO2) Nanoparticles against the Toxicity of Leishmania Tropica in Adult Albino Male Rats - Ahmed Hamad Saleh (Journal of Global Pharma Technology, 2016)
The present study was designed to show the role of green Tio2 nanoparticles against toxicity of Leishmania tropica. The present study used 15 adult albino male rats that divided randomly to following groups (each group consist 5 rats); control group received ad libidium, second group infected with Leishmania tropic, third group treated with 50ug/kg green Tio2 nanoparticles. Oxidative stress and antioxidant parameters in positive group injected show significant increased (P < 0.05) in levels of MDA (malonedialdehyied) and significant decreased (P < 0.05) in levels of glutathione (GSH) and catalase compared with control group. While, after used green Tio2 nanoparticles, the results showed non-significant changes (P < 0.05) in MDA, GSH and catalase levels showed non-significant changes (P < 0.05) compared with control group. Histological study of skin in positive group show severs lymphocytes infiltration between collagen fibers in dermis layer with oedema. On other hand, skin in treated group show  epidermis layers normal with dermis appear normal with normal distributed of collagen fibers and hair follicles. It was concluded that green Tio2 nanoparticles has been potential role against toxicity of Leishmania tropica in male rats.Keywords: Tio2 nanoparticles; Leishmania tropica; Oxidative stress; Antioxidant factors.